Sports tourism in Oporto as a destination: The influence of FC Porto Football Club - Liberato, Dália (2019)
Created in 1893, and with over 125 years of history and accomplishments, the FC Porto is one of the world’s most spoken and most successful sports clubs. Due to its path of victories, trophies, prizes, and its growing importance and growth at national and international level, a study was developed that relates Sports Tourism in the Oporto, and that analyses, in particular, the influence of the club in the city of Oporto, with the reference of two unavoidable equipments of the city, the Dragão Stadium and the FC Porto Museum. The city of Oporto has also been registering a remarkable growth path, as a tourist destination, besides the classification of its historical centre, considered by UNESCO as a World Heritage. It has carried out a relevant work, since 2001, as the European Capital of Culture, which ensured, partly, the award of Best European Destination in 2012, 2014 and 2017. The DMOs, either regional and municipal have developed a partnership path with local institutions and entities, being this decisive for the maintenance of the competitiveness as a tourist destination. The overall scope of this study is to perceive the role of football, in particular, the FC Porto football club, in Oporto as a tourism destination. To respond to the research objectives, a qualitative methodology was used, where semi-structured interviews were applied to four personalities and that allowed the collection of descriptive data in the language of the interviewees themselves, about the topic of Sports Tourism and the destination of Oporto. This study intends to be an important contribution to the scientific literature in the field of sports tourism, namely in the relationship between the FC Porto football club and Oporto tourism destination, for the definition of future strategies bearing in mind collaboration and strengthening partnerships in a competitive perspective for both. The data gathered confirm that the Oporto brand influences the potential of Oporto city as a sports tourism destination, and the importance and perception of FC Porto football club in Oporto as a destination, influence the average stay and with whom tourists travel, as well as the main activities carried out during the trip.